Vaccination compliance of selected childhood immunization programs and the socio-determinant factors in Nigeria - Oluyemi A Okunlola; Olawunmi R Oyerinde; Imisioluwa D Fashina; Oyetunde T Oyeyemi (Journal of Infection in Developing Countries)
Introduction: Adherence to full vaccination is important in preventing childhood diseases. The aim of this study was to evaluate the level of compliance to full vaccination and identify the socio-cultural factors associated with full vaccination compliance in children.